STRATEGY TO IMPROVE BRAND AWARENESS - Liando, Monica Francesca; Setyawati, Christina Yanita (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
Brand strategy is an important thing that has to be built by the company to strengthen the relationship between a company and its customers to provide benefits for the company so that the company is able to win the competition in the industry (Sadat, 2009). Wheeler (2013) explains that the company can create a brand strategy to provide a strong sense so that it can compete with the competitors. The development of creative industries in Indonesia made a great contribution in the economy of Indonesia where the craft sector became the biggest contributor (Indonesia Kreatif, 2014). Companies which engaged in the craft sector are increasing, so that the companies face intense competition. It means that the company needs to build a brand that build good perception and gain the trust of the customers. This study aims to find strategies that can increase brand awareness by conducting case study on Empress Box company. Empress Box that founded in January 2014 is a company engaged in the creative industries. The company produce exclusive jewelry made of silver. The method used in this study is a qualitative with case study approach. The result of this study suggest three strategies. The first strategy that can increase brand awareness is the brand building characteristics that determine the segmenting, targetting, and positioning. The second strategy is to do integrated marketing communication (IMC), by using social media, joining competitions and exhibitions. The third strategy is product placement by doing endorsements and displaying the products in multibrand stores.